THE ROLE AND POSITION OF NUAULU WOMEN IN THEIR ANCIENT CULTUREON SERAM ISLAND, CENTRAL MALUKU - Lodewyk Nahuway; Johan Tanamal (Pedagogic Research-Applied Literacy Journal, 2025)
Nuaulu people men and women from in the past Already There is settings ( customs) customs ) that have been separate role and position Woman in public Nuaulu . Teachings ancestors like This show Woman Nuaulu No Can become leader in community , women No Can become a king, a woman No Can lead an event or tradition custom Nuaulu , female No Can become head soa , woman No Can become Saniri chief , female No Can guard House customs and so on . All form prohibitions to Woman Nuaulu This in a way clear to show difference between role and position women and men Nuaulu . Reality life Woman Nuaulu in Nua Nea Country is located in one transition awareness that role they limited / weak / low from men , even though method think they the more complex with current developments .​ Study This discuss about roles and positions Woman ethnic group Nuaulu in culture ancestors which has been maintained from generation to generation until now. Study This uses a qualitative method with a descriptive approach. Data collection through in-depth interviews with informants and observations looking at the roles and positions Woman Nuaulu in traditional ceremony / ritual process Nuaulu tribe. The results of the study showed that The role and position of Nuaulu women in Nuaulu traditions and traditional rituals cannot be separated from ancestral beliefs which have become guidelines and teachings from generation to generation for the Nuaulu people. that is birth ceremonies, hair-shaving ceremonies ( Tihti Kuau ), girls' coming-of-age ceremonies ( pinamou ), boys' coming-of-age ceremonies ( pahateri ), marriage ceremonies, and death ceremonies (autotu nimoe). which shows role and position Woman Nuaulu in a way customs are regulated based on customary ritual processions , namely demands women 's customs given authority For implement it and demand custom in the form of prohibition custom or taboo for Woman For follow as well as in its activities . While for teenage/adult women who are not yet married or still in school, their roles and positions they are more interested in the development of modernization, concentrate on their education , TV information, android phones (face book, WA, Youtube), and they still obey the norms and values of customs that have been taught by parents, and traditional figures. While for women who are already married, they still carry out all customary provisions with all the processions of traditional ceremonies from birth to death (life cycle) and they are afraid of violating customary rules because of the sanctions (ancestral sanctions). They do not want to go against customary provisions because it has a disastrous or unfortunate impact on women, families and society.